Appropriating the closure of Jesuit missions: Fritz Hochwälder's Das heilige Experiment - F. Hale (Acta Theologica)
Since the eighteenth century the history of the Jesuit missionary endeavours in South America, especially their forced closure in 1760s, has been used rhetorically by writers in several genres, providing them with historical evidence to support a variety of latter-day causes. During the Second World War the Viennese Jewish playwright Fritz Hochwälder, then living in exile in Switzerland, followed in this tradition when he wrote his tragedy, Das heilige Experiment. It was a timely plea for toleration and religious freedom. Though almost completely ignored in histories of the Society of Jesus, this work vividly illustrates how a dramatic event in the history of Christianity can speak to subsequent issues.